PRIORITY NEEDS FOR DEVELOPING HUMAN RESOURCES MANAGEMENT FOR ENHANCING ORGANIZATIONAL COMMITMENT OF TEACHERS IN THE PAKHEENOPPAWAT CONSORTIUM UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE BANGKOK 2 - Suphajalasaya, Bheme; Charoenkul, Nantarat (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aimed to study the current and desired conditions of human resources management for enhancing organizational commitment of teachers in the Pakheenoppawat Consortium under the Secondary Educational Service Area Office Bangkok 2, and investigate the priority needs for developing human resources management for enhancing organizational commitment of teachers in the Pakheenoppawat Consortium under the Secondary Educational Service Area Office Bangkok 2. The study employed a survey research approach. The population included 9 school principals and 9 deputy directors responsible for human resource management selected through purposive sampling and 252 teachers selected using stratified random sampling, totally 270. Data were collected using a questionnaire with a high reliability coefficient (Cronbach’s Alpha = 0.945). Data analysis involved frequency, percentage, mean, standard deviation, and Modified Priority Needs Index (PNIModified). The research findings revealed as follows; The overall current state of human resources management for enhancing organizational commitment of teachers in the Pakheenoppawat Consortium under the Secondary Educational Service Area Office Bangkok 2 was at a moderate level. The aspect of teacher development had the highest average, which was at a high level. The overall desired state of human resources management for enhancing organizational commitment of teachers in the Pakheenoppawat Consortium under the Secondary Educational Service Area Office Bangkok 2 was at the highest level. The aspect of compensation and welfare had the highest average, which was at the highest level. And the overall priority needs for developing human resources management for enhancing organizational commitment of teachers in the Pakheenoppawat Consortium under the Secondary Educational Service Area Office Bangkok 2 was 0.373 (PNIModified = 0.373). The aspect with the highest priority needs index was performance appraisal (PNIModified = 0.412), followed by compensation and welfare (PNIModified = 0.370) and teacher development had the lowest priority needs index (PNIModified = 0.337).